The primary stability of two dental implant systems in low-density bone. Issue 8 (August 2022) - Heitzer, M.; Kniha, K.; Katz, M.S.; Winnand, P.; Peters, F.; Möhlhenrich, S.C.; Hölzle, F.; Modabber, A.
Abstract: Primary stability in low-density bone is crucial for the long-term success of implants. Tapered implants have shown particularly favourable properties under such conditions. The aim of this study was to compare the primary stability of tapered titanium and novel cylindrical zirconia dental implant systems in low-density bone. Fifty implants (25 tapered, 25 cylindrical) were placed in the anterior maxillary bone of cadavers meeting the criteria of low-density bone. The maximum insertion (ITV) and removal (RTV) torque values were recorded, and the implant stability quotients (ISQ) determined. To establish the isolated influence of cancellous bone on primary stability, the implantation procedure was performed in standardized low-density polyurethane foam bone blocks (cancellous bone model) using the same procedure. The primary stability parameters of both implant types showed significant positive correlations with bone density (Hounsfield units) and cortical thickness. In the cadaver, the cylindrical zirconia implants showed a significantly higher mean ISQ when compared to the tapered titanium implants (50.58 vs 37.26; P < 0.001). Pearson analysis showed significant positive correlations between ITV and ISQ ( P = 0.016) and between RTV and ISQ ( P = 0.035) for the cylindrical zirconia implants; no such correlations were observed for the tapered titanium implants. Within the limitations of this study, the results indicate that cylindrical zirconia implants represent a comparable viable treatment option to tapered titanium implants in terms of primary implant stability in low-density human bone.